2020
DOI: 10.1007/s10815-020-01691-z
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of allergy in patients undergoing in vitro fertilization and embryo transfer

Abstract: Purpose To determine the prevalence of allergy in couples undergoing in vitro fertilization (IVF) and the relationship between having allergy and IVF treatment outcomes. Design A retrospective cohort study of female infertility patients aged 20-49 years and their male partners undergoing IVF cycles from August 2010 to December 2016 in an academic fertility program. Results Prevalence data was collected for 493 couples (935 cycles). Over half of the female patients (54%) had at least one reported allergy versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 39 publications
7
11
0
Order By: Relevance
“…However, one study reported similar results in both groups. 6 Regarding fertility and parity, no differences were found, which was in line with published data. 2,11,17 Although others have reported controversial results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, one study reported similar results in both groups. 6 Regarding fertility and parity, no differences were found, which was in line with published data. 2,11,17 Although others have reported controversial results.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple gestation was the main cause in patients with respiratory allergies, highlighting the possible relation between allergy and fertility, as previously mentioned. 2,6 For instance many of these patients were older, needed IVF, and waited to have their comorbidities under control. Other indications showed similar results to the general population.…”
Section: Gina Classification Bmentioning
confidence: 99%
See 1 more Smart Citation
“…However, allergy was not found to be associated with in vitro fertilization (IVF) cycle outcomes. 26 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of allergy among patients seeking infertility treatment is high compared with the general population [ 76 ]. Air-bone allergens can cause chronic airway inflammation, constriction and asthma.…”
Section: Allergic-asthma and Hypoxiamentioning
confidence: 99%